Simulation of PEM Electrolyzer Power Management with Renewable Generation in Owerri, Nigeria - MacMatthew C. Ahaotu; Chisom E. Ogbogu; Jesse Thornburg; Isdore Onyema Akwukwaegbu (Energies)
Proton exchange membrane electrolyzers are an attractive technology for hydrogen production due to their high efficiency, low maintenance cost, and scalability. To receive these benefits, however, electrolyzers require high power reliability and have relatively high demand. Due to their intermittent nature, integrating renewable energy sources like solar and wind has traditionally resulted in a supply too sporadic to consistently power a proton exchange membrane electrolyzer. This study develops an electrolyzer model operating with renewable energy sources at a highly instrumented university site. The simulation uses dynamic models of photovoltaic solar and wind systems to develop models capable of responding to changing climatic and seasonal conditions. The aim therefore is to observe the feasibility of operating a proton exchange membrane system fuel cell year-round at optimal efficiency. To address the problem of feasibility with dynamic renewable generation, a case study demonstrates the proposed energy management system. A site with a river onsite is chosen to ensure sufficient wind resources. Aside from assessing the feasibility of pairing renewable generation with proton exchange membrane systems, this project shows a reduction in the intermittency plaguing previous designs. Finally, the study quantifies the performance and effectiveness of the PEM energy management system design. Overall, this study highlights the potential of proton exchange membrane electrolysis as a critical technology for sustainable hydrogen production and the importance of modeling and simulation techniques in achieving its full potential.